Accuracy of four-dimensional CT angiography in detection and characterisation of arteriovenous malformations and dural arteriovenous fistulas. Issue 4 (August 2015) - Biswas, Shubhabrata; Chandran, Arun; Radon, Mark; Puthuran, Mani; Bhojak, Maneesh; Nahser, Hans Christean; Das, Kumar
A retrospective review was made to assess the accuracy of four dimensional CT angiogram (4D-CTA) in diagnosis of arteriovenous malformations (AVM) and dural arteriovenous fistulas (DAVF), with catheter-based digital-subtraction angiogram (DSA) being gold standard. 33 pairs of investigations (DSA and 4D-CTA) were performed primarily for suspicion of AVM/DAVF. Based on blinded reports, sensitivity and specificity for detection of AVM/DAVF were 77% (95% CI: 46 - 95%) and 100% (95% CI: 83 - 100%) respectively. Positive predictive value was 100% (95% CI: 69 - 100%) and negative predictive value 87% (95% CI: 66-97%). 4D-CTA is a practical minimally-invasive technique for evaluating cerebrovascular pathologies. There is good agreement between the findings of 4D-CTA and DSA despite the differences in temporal and spatial resolutions. 4D-CTA may obviate the need for DSA in a subgroup of patients who would otherwise have undergone this invasive investigation, which carries a risk of important complications.